Speech, Writing, and Sign A Functional View of Linguistic Representation - Baron, Naomi S. (Indiana University Press, 1980)
Linguistics has traditionally dealt with questions about structure-what are the parts of a language and how are they assembled? Naomi Baron adopts a new approach by asking what a human language is used for and how it achieves its goals. She carefully examines what is communicated, why it is important. and how the exchange is accomplished. In the process of this basic redefinition, she fashions a lucid, systematic introduction to the study of linguistics. The initial chapters discuss language as a source and solution to problems of human communication, the various aspects of representation, the definition of human language, and a methodology for the functional analysis of language. The three chapters that follow fully explore this functional perspective for spoken, written, and signed languages, and offer new evidence to demonstrate the effect of social context on linguistic structure. Speech, Writing, and Sign is profusely illustrated with drawings, photographs, and reproductions of artistic examples. Written to be accessible to beginning students, this book will also interest linguistic scholars because of its challenges to current linguistic theory.